2013
DOI: 10.1371/journal.pone.0078921
|View full text |Cite
|
Sign up to set email alerts
|

Serum Based Diagnosis of Asthma Using Raman Spectroscopy: An Early Phase Pilot Study

Abstract: The currently prescribed tests for asthma diagnosis require compulsory patient compliance, and are usually not sensitive to mild asthma. Development of an objective test using minimally invasive samples for diagnosing and monitoring of the response of asthma may help better management of the disease. Raman spectroscopy (RS) has previously shown potential in several biomedical applications, including pharmacology and forensics. In this study, we have explored the feasibility of detecting asthma and determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 46 publications
(30 reference statements)
0
62
0
Order By: Relevance
“…16 This Raman system consists of laser (785 nm, Process Instruments) as an excitation source and HE-785 spectrograph (Horiba-JobinYvon, France) coupled with CCD (Synapse, HoribaJobin-Yvon) as dispersion and detection elements, respectively. Optical¯ltering of unwanted noise, including Rayleigh signals, is accomplished through \Superhead", the other component of the system.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…16 This Raman system consists of laser (785 nm, Process Instruments) as an excitation source and HE-785 spectrograph (Horiba-JobinYvon, France) coupled with CCD (Synapse, HoribaJobin-Yvon) as dispersion and detection elements, respectively. Optical¯ltering of unwanted noise, including Rayleigh signals, is accomplished through \Superhead", the other component of the system.…”
Section: Instrumentationmentioning
confidence: 99%
“…Details of the spectral preprocessing are mentioned elsewhere. 16 Average spectra were computed from these background-subtracted and interpolated spectra. The typical spectra were baseline-corrected by¯tting a¯fth-order polynomial function using LabSpec 4.18 (Horiba Jobin Yvon, France).…”
Section: Spectra Pre-processingmentioning
confidence: 99%
“…9 The RS, which can provide chemical fingerprint/ biochemical profile, has shown promising results in the diagnosis of several cancers, 8,[10][11][12][13][14][15] including oral cancers. [16][17][18][19][20][21][22][23][24][25] Both ex vivo and in vivo RS studies in oral cancers have shown classification of pathological conditions along with detection of confounding factors like age-related changes and early events like cancer field effects in oral cancer, 16,17,[21][22][23][24][25] demonstrating efficiency of the technique. Still, further studies in exploring sequential changes in oral carcinogenesis are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…190 Other diseases or conditions that have been studied using plasma include brain ischemia (insufficient blood flow to the brain), 191,192 hepatitis C (disease of the liver), 193 pemphigus vulgaris (skin disease) 194 and preeclampsia (a condition that can occur during pregnancy). 195 Early investigations of plasma in asthma (lung inflammation) 196 and Alzheimer's disease (a form of dementia) 197,198 have also been performed.…”
mentioning
confidence: 99%